Analysis of The Marriage Treaty and Legal Approach Due Judging from The Draft of Civil Code - Takwim Azami; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The continued development of the situation in society at large prospective marriage couples who decided to make a marriage agreement. This is because both the men and women capable of generating wealth each and there are many other reasons why it made a pact to marry. Mating agreement is the agreement made by two people (prospective husband and wife) before marriage. Mating Agreement provided for in article 29 of Act No. 1 of 1974 marriage but with the birth of the constitutional court's decision No. 69 / PUU-XIII / 2015 there are some changes in the Marriage Covenant which is still a Pro Cons in society. The problems examined in this study is: how marital agreement in terms of the book of Civil Law. The method used is a normative legal approach. Source materials used law is the source of primary legal materials and sources of secondary legal materials such as books and law legal materials collection techniques performed by the document study reading and studying the legislation regulations. The analysis of legal materials in this study, conducted by processing and analyzing qualitative and descriptive poured. The result of the first conclusion that the arrangement agreement are married in Indonesia in the Act including the Civil Code, the Marriage Act No. 1 of 1974, KHI and the Constitutional Court Decision No. 69 / PUU-XIII / 2016.Keywords: Marriage Agreement; Effects; Legal Approach